2013
DOI: 10.1523/jneurosci.0780-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin Signaling in the Brainstem Influences Vagal Outflow to the Stomach

Abstract: Activation of melanocortin 4 receptors (MC4-Rs) in brain nuclei associated with food intake profoundly influences consummatory behavior. Of these nuclei, the dorsal motor vagal nucleus (DMV), which has a dense concentration of MC4-Rs, is an important regulator of gastric tone and motility. Hence, the present study sought to examine the role of MC4-Rs in this nucleus on these activities. Using an in vivo approach, MC4-R agonists, melanotan-II (MT-II) or ␣-melanocyte stimulating hormone (␣-MSH), were unilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…MC4Rs in the NTS may therefore respond to melanocortins produced locally to reduce food intake [89]. Instead, the PVH-DMV projection may modulate gut reflexes and gastric processes [90]. …”
Section: Role In Food Intakementioning
confidence: 99%
“…MC4Rs in the NTS may therefore respond to melanocortins produced locally to reduce food intake [89]. Instead, the PVH-DMV projection may modulate gut reflexes and gastric processes [90]. …”
Section: Role In Food Intakementioning
confidence: 99%
“…While details of the neuroanatomy and function of MC4R in the DMV remain to be determined (e.g. see (Richardson et al, 2013), caudal brainstem administration of melanocortin agonists inhibits food intake (Grill et al, 1998; Williams et al, 2000), and injection of melanocortin agonists into either the DMV or NTS decreases phasic gastric contractions (Richardson et al, 2013). Stereotaxic injections of melanocortin agonists, MT-II or α-MSH into either the DMV or the NTS can modulate gastric activity via vagal outflow to the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotaxic injections of melanocortin agonists, MT-II or α-MSH into either the DMV or the NTS can modulate gastric activity via vagal outflow to the stomach. This effect was blocked by administration of melanocortin antagonist SHU9119, vagotomy, or knockout of the MC4R (Richardson et al, 2013). Thus, the melanocortin system is likely to affect food intake not only through effects on behavioral centers in the CNS, but also secondarily through MC4R signaling involved in the postprandial functions of the enteric nervous system (ENS) (Gautron et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…*Significantly different (P Յ 0.05) from saline control treatment. edly is inhibitory (44,51). We found that MTII-induced ERK1/2 phosphorylation in the DMV was attenuated by an NMDAR antagonist, indicating that DMV ERK1/2 phosphorylation requires NMDAR activation.…”
Section: Discussionmentioning
confidence: 65%
“…From these data, one might be tempted to postulate a role for vagal efferents in the reduction of food intake by MTII. While NTS injection of MC4R agonists has been shown to modulate gastric activity (44), vagal efferents are not likely to play a role in MTIIinduced reduction of food intake. Williams et al (60) clearly demonstrated that vagotomy, which results in degeneration of peripheral endings of vagal efferents, does not attenuate reduction of food intake by fourth ventricle MTII.…”
Section: Discussionmentioning
confidence: 97%